Beyond the Veil: A Phenomenology of the Educational Gaze - Pantrini, Paolo (Encyclopaideia, 2023)
This paper moves from an educator’s experience with people with strong disability and from his trouble to grasp the hidden potential of the subject, almost covered by precomprehension and prejudice, that like a sort of veil of Maya prevent him from seeing the implicit resources residing within everyone. It is argued that the educator must gain a phenomenological stance which allows him to go beyond the experience of limits towards the very essence of the person. The educator’s gaze arises from a path of awareness and personal growth, capable of revealing the authentic meaning of the educational act. Ispiring to the narrations of some literary figures, the main characteristics of the educational gaze are outlined here, in terms of a way of being-in-the-situation, capable of wonder and astonishment, attention to details and untiring search for meaning.